IMPORTANCE OF ACTION GAMES IN TEACHING ENGLISH TO PRIMARY SCHOOL STUDENTS. (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article focuses on effective and interesting games based on interactive methods to increase the interest of elementary school students in learning English.